Work-life systems: rethinking endurance and uncertainty in future work - Griffin, Mark (2018)
The nature of work is rapidly evolving as technological, demographic, and economic changes influence all aspects of our society. The changing nature of work requires a more wholistic understanding of work life systems that encompasses work tasks, non-work, and sleep across longer time spans. In this presentation I explore two concepts through which research is extending the understanding of work-life systems.